Ovarian function and response to estrus synchronization in Creole cattle in Mexico. Review - Pérez Ruiz, Elizabeth; Carrera Chavez, Jose Maria; Quezada Casasola, Andres; Alvarez Holguin, Alan; Ochoa Rivero, Jesús Manuel; Chávez Ruiz, Manuel Gustavo; Román Ponce, Sergio Iván (2022)
Nowadays, reproductive biotechnologies have made it possible to conserve and use animal genetic resources. One of these technologies is the estrus synchronization programs, which allow programming the time for mating according to the availability of fodder or the birth of calves for commercial purposes. Another application is the reduction of the calving- first ovulation interval through protocols that facilitate the use of artificial insemination. Creole cattle are a valuable genetic resource due to their hardiness and adaptability to difficult environmental conditions; they are resistant to parasites, take advantage of available forage resources and reproduce in systems with little or no supplementation. In Mexico, the first studies of synchronization of Creole cattle suggest that Creole cows do not respond adequately to hormonal protocols and gestation percentages lower than those obtained in other breeds are obtained. The foregoing gave rise to a series of studies on reproductive physiology and the use of biotechnologies in Creole cattle. The objective of this review is to collect existing information on the use of estrus and ovulation synchronization protocols in Creole cattle from Mexico; in order to be able to identify the lines of research necessary for the development of estrus and ovulation synchronization protocols suitable for Creole cattle.